Adaptive damper control for HVAC systems based on human occupancy and indoor parameters: A development study - Vasanthkumar, C. H.; Roselyn, J. Preetha; Uthra, R. Annie; Devaraj, D. (Frontiers in Energy Research, 2022)
Occupancy-based strategies for the control of ventilation systems in buildings are effective for achieving energy savings and user comfort. Savings in energy consumption of more than 50% can be achieved by controlling heat, ventilation, and air conditioning (HVAC) systems with accurate sensory and occupancy information. In this study, the flow through the damper of the variable area valve (VAV) system and the speed of the blower’s variable frequency drive (VFD) are controlled in the HVAC system, on the basis of human occupancy and indoor parameters, namely, temperature and humidity, segment-wise in the building. In the proposed model, the flapper angle of the VAV is estimated using the indoor temperature, external temperature, and number of occupants. The occupancy data are fed to the controller proposed to regulate the flow through the ducts of the system, which is based on the flapper angle of the VAV, in order to maintain human comfort. The proposed scheme makes it possible to detect abnormalities in energy utilization and to trace maximum utilization in the building based on occupancy, with the control parameters of the HVAC adjusted for a comfortable indoor environment. Performance evaluation of the VAV system with its proposed control strategy, temperature, and flow distribution is simulated using Fluent software. A laboratory grade prototype incorporating the proposed control strategy is then developed, tested under three different conditions, and the results are reported. The experimental results show that an energy saving of 18% can be achieved.